Atividades antimicrobiana, antibiofilme e antiproliferativa do extrato de Guaripa graciliflora Mart. E do óleo essencial de Schinus terebinthifolius Raddi - Alves, Érika Ponchet (2015)
Medicinal plants represent a promising source of active compounds which can be used in the development of new drugs. There is a diversity of plants that are used by the population for therapeutic purposes, among which are the Guapira graciliflora Mart., popularly known as “joão-mole”, and Schinus terebinthifolius Raddi, known as “aroeira-da-praia”. These plants stand out in folk medicine due to its therapeutic properties in inflammatory and infectious processes. This study evaluated in vitro antimicrobial and antiproliferative activities besides, toxicity and chemical composition of the hydroalcoholic extract of the leaves of G. graciliflora. and the essential oil from unripe fruits of S. terebinthifolius. Antimicrobial activity was evaluated by microdilution technique in broth, with determination of minimum inhibitory concentration (MIC) and bactericidal/ Fungicide minimum concentration (MBC / MFC) using to bacterial strains: Staphylococcus aureus ATCC 6538, Escherichia coli ATCC 11775 and Salmonella enteritidis ATCC 13076, and the yeast Candida albicans ATCC 10231. The extracts were analyzed againstC. albicans biofilm after 48 hours of expositions, by means of the CFU / ml count and examination of cell morphology byfluorescence microscope (FM) using Calcofluor White. The antiproliferative activity was evaluated against nine tumor cell lines (U251, MCF7, NCI / ADR-RES, 786-0, NCI-460, HT29, K562, and PC-03 OVCAR-3) and a non-tumor cell line of keratinocytes (HaCat ). Preliminar toxicity was evaluated through the hemolysis assay. Phytochemical analysis of the extract G. graciliflora was performed by thin-layer chromatography, and the essential oil of S. terebinthifoliuswas analysed by Gas Chromatography hifenized with Mass Spectrometry (GC-MS). The G. graciliflora andS. terebinthifoliussamplesshowed potential antifungal against C. albicans with the MIC values of 0.25mg/mL and 1mg/mL, respectively, and no antibacterial activity (MIC>2mg/mL). Both samples (1mg/mL) reduced the number of CFU/mL of C. albicans biofilm. In fluorescence microscopy it was, observed the maintenance of cellular architecture of C.albicansafter the treatments. The G. gracilifloraextract presented cytocidal effect for all cells of the tumor lines except for the K562 (leukemia) while the essential oil of S. terebinthifolius proved cytocidal for all strains. Both samples did not produce hemolysis over 50% up to a concentration of 16mg/mL. Phytochemical analysis of the extract G. graciliflora revealed the predominance of flavonoid compounds, and the major compound identifiede onS. terebinthifolius essential oil were to, terpene, alpha- and beta- phellandrene. The extract from the leaves of G. graciliflora and the essential oil of the fruit of S. terebinthifolius showed potential antifungal against C. albicans in their planktonic form and organized in biofilms; besides antiproliferative activity across the human tumor cell lines and low toxicity on red blood cells. They have been considered promising sources of active compounds, for product development and medicine, anticandida and antiproliferative action. This way, other studies may extend these results, aiming the development to the studies of herbal medicines to clinical use.